2018
DOI: 10.1007/s10389-018-0916-6
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among older European adults: results from the survey of health, aging and retirement in Europe

Abstract: Purpose Previous research has suggested that individuals are mostly prone to loneliness in their later years of life due to being exposed to several risk factors typical of old age. The current study aims to examine possible demographic, health and social determinants of loneliness among older adults in Europe. Methods Data on a nationally representative sample of 5,074 Europeans aged ≥65 years were drawn from the first wave of the Survey of Health, Aging and Retirement in Europe (SHARE, 2004/2005). Frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 57 publications
10
60
1
6
Order By: Relevance
“…Many studies on the impact of fertility on later-life loneliness compared parents and their childless counterparts (e.g., Hansen et al 2009;Koropeckyj-Cox 1998;Van den Broek 2017;Vozikaki et al 2018;Zhang and Hayward 2001). Scholars assessing loneliness differences among parents have tended to focus on the role of differences in the frequency of contact with children (Fokkema et al 2012;Pinquart 2003;Routasalo et al 2006), the quality of the relationship with children (Koropeckyj-Cox 2002;Long and Martin 2000) or the geographical distance to children (Van den Broek and Grundy 2017).…”
Section: Observational Studies Selection and Reverse Causality Biasmentioning
confidence: 99%
“…Many studies on the impact of fertility on later-life loneliness compared parents and their childless counterparts (e.g., Hansen et al 2009;Koropeckyj-Cox 1998;Van den Broek 2017;Vozikaki et al 2018;Zhang and Hayward 2001). Scholars assessing loneliness differences among parents have tended to focus on the role of differences in the frequency of contact with children (Fokkema et al 2012;Pinquart 2003;Routasalo et al 2006), the quality of the relationship with children (Koropeckyj-Cox 2002;Long and Martin 2000) or the geographical distance to children (Van den Broek and Grundy 2017).…”
Section: Observational Studies Selection and Reverse Causality Biasmentioning
confidence: 99%
“…There is no consensual definition of loneliness in the literature, although many authors (Ong et al, 2016) consider that loneliness refers to a negative experience that occurs when there is a discrepancy between desired and established social relations (Domènech-Abella et al, 2017;Lasgaard et al, 2016;Perlaman & Peplau, 1981;Vozikaki et al, 2018). Loneliness has been associated with an increased risk of mortality (Holt-Lunstad et al, 2015;Luo et al, 2012;Perissinotto et al, 2012;Shiovitz-Ezra & Ayalon, 2010) and identified as an important risk factor for health (Courtin & Knapp, 2017;Holt-Lunstad et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, loneliness becomes an important (or a major) issue as individuals grow older (Dahlberg et al, 2015;Savikko et al, 2005;Vozikaki et al, 2018) and is associated with a set of other sociodemographic, economic, health, social and cultural characteristics (Aartsen & Jylhä, 2011;Dahlberg et al, 2015;Dahlberg & Mckee, 2014;Drageset et al, 2012;Dykstra, 2009;Fokkema et al, 2012;Hansen & Slagsvold, 2016;Houtjes et al, 2014;Perissinotto et al, 2012;Pinquart & Sorensen, 2001;Prieto-Flores et al, 2011;Savikko et al, 2005;Shiovitz-Ezra, 2013;Vozikaki et al, 2018;Zebhauser et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It appears counterintuitive that, within Europe, levels of later-life loneliness tend to be higher in regions in which levels of family contact and co-residence between older parents and their children are also higher (Vozikaki et al 2018;Yang/Victor 2011). However, in more 'family orientated' societies (Reher 1998), such as those of Southern and Eastern Europe (Daatland/Herlofson/Lima 2011), individuals who lack important family resources may have fewer alternative sources of support and social interaction.…”
Section: Theoretical Backgroundmentioning
confidence: 99%